Development of artistic pottery traditions - Abdusalomov Baxtiyor Ubaydullaevich (Zien Journals, 2022)
History of the issue. An has passed an important stage of the development of traditional ceramics. It was distinguished by progressive processes; it was distinguished by support for the participation of the state and the community in the fate of craftsmanship, measures to preserve the traditional foundations of folk craftsmanship, and the addition of organizational forms of production that matched research and social and economic situations.
Keywords: Ceramics; industry; artist; craftsman